Putera - Julie Dahlan; Zulkeflie M. Osman ([S.l.] : J.D. Productions [production company] ; Kuala Lumpur : Associated Video [distributor])
Sebuah filem Melayu arahan Zulkeflie M. Osman
Penerbit eksekutif, Linda Zainuddin ; penyunting, Mariam Ibrahim ; skrip, Anwar Idris ; jurukamera, Nuri Harmaini
Vaneeda Imran, Joe'Wing', Erma Fatima
Keywords: Motion pictures -- Malaysia; Malay drama; Love in motion pictures